Understanding effective approaches to promoting mental health and preventing mental illness - McDaid, David (OECD Health Working Papers, 2017)
The health, social and economic consequences of poor mental health are substantial. More attention is focusing now on the development of actions to promote better mental health and wellbeing and prevent mental ill-health. This paper provides an overview of the development of approaches to promoting mental wellbeing and preventing mental ill-health in OECD countries, together with an assessment of what is known on their effectiveness and cost effectiveness. The paper finds that there is a sound and quite extensive evidence base for effective and cost effective actions which can promote mental wellbeing and prevent mental ill-health. However, the existence of actions and programmes in mental health promotion and prevention is uneven both between countries, and across different points of the life course. Many countries could stand to scale-up their promotion and prevention efforts in the mental health field, and further efforts are particularly needed to introduce interventions targeted at unemployed and older populations